Assessment and promotion policies of entrepreneurship in students - Oliver, Amparo; Galiana, Laura; Gutiérrez-Benet, Marta (Anales de Psicología / Annals of Psychology, 2015)
The increasing need for socio-economical and educative measures, targeting the development of an entrepreneurship culture, makes essential the accurate definition of the construct. This, together with a measure to provide a baseline of students’ entrepreneurship would facilitate the assessment of European and state government policies and interventions. The aim of the study is to provide an understanding of the entrepreneurial attitudes in the Spanish educative context, from which the implementation and assessment of entrepreneurship culture and education programs could be developed. 524 students (267 high school and 257 university students) answered the Entrepreneurship Attitudes Scale. Descriptive statistics and parametric and non-parametric multivariate analyses of variance were developed, including gender and educational stage as independent variables. Results showed differences between genders on some entrepreneurship dimensions, and also offered criteria values for future research and interventions in the field. Implications of this work are related to the current political context.